Living Sacramentally in a Political World: Towards a Sacramental Political Ontology - Tautz, Stephan (Concilium, 2025)
Following de Lubac's famous adage "the Eucharist makes the Church", sacramental theology can be depicted as the political theology of the Church. While the article develops such a political reading of sacramentality in a first step, it demonstrates in a second step how the postmodern condition leads to a non-foundational relecture of both sacramentality and the political. On this basis, it then outlines a possible theo-political sacramental ontology for our present condition, drawing on current developments in natural theology as a way to interpret sacramentality, both politically and ontologically.